2017
DOI: 10.1111/joic.12446
|View full text |Cite
|
Sign up to set email alerts
|

A practical guide to cardiovascular 3D printing in clinical practice: Overview and examples

Abstract: The advent of more advanced 3D image processing, reconstruction, and a variety of three-dimensional (3D) printing technologies using different materials has made rapid and fairly affordable anatomically accurate models much more achievable. These models show great promise in facilitating procedural and surgical planning for complex congenital and structural heart disease. Refinements in 3D printing technology lend itself to advanced applications in the fields of bio-printing, hemodynamic modeling, and implanta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…Thus, postprocessing may be necessary in order to soften the printed structures. Some examples are given in the reproduction of cartilaginous tissues [25], arteries for practicing valve replacement [26], hepatic segment [27], and hearts [28]. An interesting example is the development of a 3D-printed brain aneurysm using the flexible TangoPlus™ photopolymer [29] that represented a useful tool to plan the operative strategy in order to treat congenital heart disease.…”
Section: Transformation Process and Materials Usedmentioning
confidence: 99%
“…Thus, postprocessing may be necessary in order to soften the printed structures. Some examples are given in the reproduction of cartilaginous tissues [25], arteries for practicing valve replacement [26], hepatic segment [27], and hearts [28]. An interesting example is the development of a 3D-printed brain aneurysm using the flexible TangoPlus™ photopolymer [29] that represented a useful tool to plan the operative strategy in order to treat congenital heart disease.…”
Section: Transformation Process and Materials Usedmentioning
confidence: 99%
“…Precise pre-surgical planning of CHD can be achieved with use of 3D printed models, and this is reported in recently published systematic reviews and meta-analyses and a number of other studies [13,[33][34][35][36][37][38][39][40]. Of 24 eligible studies in the systematic review conducted by Lau and Sun, 15 of them reported the 3D printed models in the pre-operative planning of CHD treatment, provided how 3D printed models assisted the planning of surgical procedures and surgeons' opinion on the 3D printed models [13].…”
Section: D Printing In Congenital Heart Diseasementioning
confidence: 99%
“…The large amount of photocured resin required to manufacture a dental model is expensive, and so various efforts have been made to reduce the resin material consumed [3]. If a part such as the palate or tongue is unnecessary to the purpose of a diagnosis or treatment, it can be removed during the premodeling process and then not printed, producing a hollow design inside the model [28,29]. Such a modeling strategy can also reduce the printing time required for the 3D printing process [2,30].…”
Section: Introductionmentioning
confidence: 99%